Generation of gold nanoclusters encapsulated in an MCM-22 zeolite for the aerobic oxidation of cyclohexane. Issue 11 (18th January 2019) - Liu, Lichen; Arenal, Raul; Meira, Debora M.; Corma, Avelino
Abstract : Au nanoclusters encapsulated in an MCM-22 zeolite are highly active for the selective aerobic oxidation of cyclohexane to KA-oil. Abstract : In this work, we will report the generation of Au clusters in a purely siliceous MCM-22 zeolite. The catalytic properties of these Au clusters have been tested for the selective oxidation of cyclohexane to cyclohexanol and cyclohexanone (KA-oil). The Au clusters encapsulated in the MCM-22 zeolite are highly active and selective for the oxidation of cyclohexane to KA-oil, which is superior to Au nanoparticles on the same support. These results suggest that Au clusters are highly active for the activation of oxygen to produce radical species.